Wavelet methods for elliptic partial differential equations - Urban, Karsten (Oxford : Oxford University Press, 2009)
A text based on the author's course that introduces graduates to the basics of wavelet methods for partial differential equations and describes the construction and analysis of adaptive wavelet methods.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wavelets (Mathematics); Differential equations, Elliptic